Use of Mobile Phone and its Apps in Extension Services - Pranav Kumar; Amandeep Singh (Journal of Agricultural Extension Management, 2017)
Information and Communication Technology (JCT) and its application have shown great prospects in remodeling extension services in both developed and developing countries. The present era is an era of science and technology and those related to these fields are showing a tremendous increase in their value and functionality. Linking extension services to emerging technologies should be focused upon for better results and efficient services, due to the fact that a majority of the people are now connected to one another through mobile phones. These devices and their apps can be used for better linkages and to provide farmers with latest information instead of creating new devices for extension activities